Ferrocene-fullerene dyad as a novel burn rate modifier for propellants - Shrutika Sriramrao; Parveen Raman; Akash Dhas; Shaibal Banerjee (Energetic Materials Frontiers, 2024)
The burn rate of composite rocket propellants serves as a critical ballistic parameter in the construction of a rocket engine. Due to their large surface areas, carbon-based materials such as carbon nanotubes, graphene, and fullerene have demonstrated promising results as burn rate modifiers (BRMs) for propellants. Unlike their inorganic counterparts, these materials, being combustible, contribute to energy output besides enhancing the burn rate. This study reported a ferrocene-fullerene dyad as a BRM prepared through the thermal decomposition of ammonium perchlorate (AP) in composite solid propellants. By incorporating 0.6 wt% of the dyad, the burn rate of the prepared propellants increased by 70%, accompanied by a rise in their calorific value.